Stem members of Platyrrhini are distinct from catarrhines in at least one derived cranial feature. Issue 100 (November 2016) - Fulwood, Ethan L.; Boyer, Doug M.; Kay, Richard F.
Abstract: The pterion, on the lateral aspect of the cranium, is where the zygomatic, frontal, sphenoid, squamosal, and parietal bones approach and contact. The configuration of these bones distinguishes New and Old World anthropoids: most extant platyrrhines exhibit contact between the parietal and zygomatic bones, while all known catarrhines exhibit frontal-alisphenoid contact. However, it is thought that early stem-platyrrhines retained the apparently primitive catarrhine condition. Here we re-evaluate the condition of key fossil taxa using μCT (micro-computed tomography) imaging. The single known specimen of Tremacebus and an adult cranium of Antillothrix exhibit the typical platyrrhine condition of parietal-zygomatic contact. The same is true of one specimen of Homunculus, while a second specimen has the 'catarrhine' condition. When these new data are incorporated into an ancestral state reconstruction, they support the conclusion that pterion frontal-alisphenoid contact characterized the last common ancestor of crown anthropoids and that contact between the parietal and zygomatic is a synapomorphy of Platyrrhini.